Preparation method of metal material for motor shaft with high bending resistance
By controlling the composition and processing parameters of the metal materials used in the motor shaft throughout the process, the problem of insufficient bending performance of the motor shaft in the prior art is solved, and the preparation of high-strength and high-toughness metal materials is realized, and the performance and reliability of the motor shaft are improved.
Patent Information
- Application Number
- CN202411992755.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-31
- Publication Date
- 2025-04-15
AI Technical Summary
The prior art is difficult to effectively improve the bending performance of the motor shaft, resulting in residual deformation and fatigue failure under the action of bending force.
Through the entire process of material composition design, preparation and deep processing, the inclusion equivalent diameter distribution in the metal materials used for motor shafts is 1 to 10 microns, the segregation index of low casting blanks is 0.95 to 1.05, the carbon increase index of low surface is 0.8 to 1.2, and the surface hardness index is 0.80 to 0.85, thereby preparing metal materials for high-strength and high-toughness motor shafts.
It improves the toughness and bending resistance of metal materials, extends the service life of the motor shaft, and reduces the occurrence of downtime or failure.
Smart Images

Figure CN119824305A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of metallurgy, and in particular to a method for preparing a metal material for a motor shaft with high bending resistance. Background Art
[0002] The bending resistance of the motor shaft refers to its ability to resist bending forces. As an important part of the motor, the motor shaft needs to withstand various alternating stresses without causing residual deformation and fatigue damage. Therefore, the bending resistance is a key indicator that needs to be considered during the design and manufacturing process of the motor shaft. Summary of the invention
[0003] The purpose of the present invention is to overcome the defects of the above-mentioned prior art and provide a method for preparing a metal material for a motor shaft with high bending resistance.
[0004] The present invention solves the technical problem by adopting the following technical solutions.
[0005] The present invention provides a method for preparing a metal material for a motor shaft with high bending resistance, which comprises: carrying out control over the entire process from material composition design, preparation and deep processing, so that the equivalent diameter of inclusions in the metal material for the motor shaft is distributed in the range of 1 to 10 microns, the low ingot segregation index is in the range of 0.95 to 1.05, the low surface carbon increase index is in the range of 0.8 to 1.2, and the surface hardness index is in the range of 0.80 to 0.85, so as to prepare a metal material for the motor shaft with high strength and high toughness.
[0006] The present invention has the following beneficial effects:
[0007] The present invention provides a method for preparing a metal material for a motor shaft with high bending resistance. The present invention controls the composition of the metal material and key parameters of the production process to prepare a metal material for a motor shaft with high purity (equivalent diameter of inclusions distributed in 1-10 microns), a low ingot segregation index of 0.95-1.05, a low surface carburization index of 0.8-1.2, and a suitable surface hardness index of 0.80-0.85, thereby improving the toughness of the metal material and comprehensively realizing the preparation of a high-strength and high-toughness metal material for a high-bending motor shaft. BRIEF DESCRIPTION OF THE DRAWINGS
[0008] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the drawings required for use in the embodiments are briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present invention and therefore should not be regarded as limiting the scope. For ordinary technicians in this field, other related drawings can be obtained based on these drawings without creative work.
[0009] Figure 1 The metallographic structure of the metal material ball retreat edge prepared in Example 1;
[0010] Figure 2 The metallographic structure of the edge of the metal material prepared in Example 1 after heat treatment;
[0011] Figure 3 The inclusions in the metal material prepared in Example 2;
[0012] Figure 4 The metallographic structure of the edge of the metal material prepared in Example 3;
[0013] Figure 5 The secondary electron morphology of the fracture surface of the metal material prepared in the cold bending test of Comparative Example 1;
[0014] Figure 6 The metallographic structure of the edge of the metal material prepared in Comparative Example 1 after spheroidizing annealing;
[0015] Figure 7 The metallographic structure of the edge of the metal material prepared in Comparative Example 1 after heat treatment;
[0016] Figure 8 Inclusions in the metal material prepared in Comparative Example 2;
[0017] Fig. 9 The metal material prepared in Comparative Example 3 has edge pearlite segregation caused by carbon enhancement at the edge of the continuous casting billet. DETAILED DESCRIPTION
[0018] In order to make the purpose, technical scheme and advantages of the embodiments of the present invention clearer, the technical scheme in the embodiments of the present invention will be described clearly and completely below. If the specific conditions are not specified in the embodiments, they are carried out according to conventional conditions or conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments used is not specified, they are all conventional products that can be purchased commercially.
[0019] The following is a detailed description of a method for preparing a metal material for a motor shaft with high bending resistance provided by an embodiment of the present invention.
[0020] An embodiment of the present invention provides a method for preparing a metal material for a motor shaft with high bending resistance, which includes: carrying out management and control of the entire process from material composition design, preparation and deep processing, so that the equivalent diameter of inclusions in the metal material for the motor shaft is distributed in the range of 1 to 10 microns, the low ingot segregation index is in the range of 0.95 to 1.05, the low surface carburization index is in the range of 0.8 to 1.2, and the surface hardness index is in the range of 0.80 to 0.85, so as to prepare a metal material for a motor shaft with high strength and high toughness.
[0021] Bending resistance is a key indicator that needs to be considered during the design and manufacturing process of the motor shaft. There are many factors that affect the bending resistance, including chemical composition, organizational structure, and preparation process. High-strength metal materials can improve the bending resistance of the shaft. Medium and high carbon alloy steels are widely used in motor shafts that require higher loads and speeds due to their high strength and high wear resistance. However, under high-strength conditions, the chemical composition design of metal materials and preparation links such as smelting, solidification, processing and deep processing, due to problems such as component segregation, a large number of non-metallic inclusions, uneven organization, and material surface defects, the motor shaft will crack due to cold bending, which is not conducive to the stable operation of the motor, and it will harm production safety and quality, and cause a lot of waste of social resources.
[0022] In order to solve the above-mentioned problems existing in the prior art, an embodiment of the present invention provides a method for preparing a metal material for a motor shaft with high bending resistance, which includes: carrying out management and control of the entire process from the material composition design link, the preparation link and the deep processing link, so that the equivalent diameter of inclusions in the metal material for the motor shaft is distributed in 1 to 10 microns, the low ingot segregation index is 0.95 to 1.05, the low surface carbon increase index is 0.8 to 1.2, and the surface hardness index is 0.80 to 0.85, so as to prepare a metal material with high purity, high organizational uniformity and high surface quality, thereby improving its strength, toughness and bending resistance, increasing the service life of the motor shaft, and reducing the occurrence of shutdown accidents or failures.
[0023] In some optional embodiments, the chemical composition, by weight percentage, is as follows: C: 0.35-1.35wt%, Si: 0.10-0.50wt%, Mn: 0.1-1.5wt%, Al: 0.002-0.045wt%, N: 0.002-0.02wt%, Cu≤0.25wt%, As≤0.040wt%, Sn≤0.028wt%, P: ≤0.025wt%, S: ≤0.045wt%, and the rest is Fe and impurities.
[0024] In some optional implementations, the control of the preparation process includes: controlling the parameters of the smelting process, solidification process and forming process, and the control of the deep processing process includes: controlling the surface structure of the spheroidizing annealing and heat treatment process. Through the control of the above processes, the purity of the smelting process, the segregation and surface quality of the solidification process, the precise control of the uniformity of the rolling process, and the surface structure of the spheroidizing and heat treatment processes are achieved, and the preparation of high-strength and high-toughness metal materials for high-bending motor shafts is comprehensively achieved.
[0025] In some optional embodiments, the control of the smelting process includes: controlling the initial oxygen content of the molten steel in the primary refining furnace, controlling the initial inclusion composition and removal, and precisely controlling the aluminum content in the steel, so as to control the equivalent diameter distribution of inclusions remaining in the metal material to be 1 to 10 microns, thereby achieving purity control of the molten steel during the smelting process.
[0026] In some optional implementations, the initial oxygen content control of the molten steel in the primary refining furnace includes: controlling the initial oxygen content of the molten steel to 0.01-0.03% by improving the dynamics of the composite bottom blowing of the primary refining furnace and controlling the blowing oxygen consumption; when the initial oxygen content is higher than 0.02%, adding carbon powder for pre-deoxidation in equal proportion; the initial inclusion composition and removal control includes: in the early stage of the primary refining furnace, the addition of deoxidizers quickly forms high-melting-point high-alumina and high-silicon oxide inclusions, which are quickly collided, aggregated, and floated for removal; the precise control of the aluminum content in the steel includes: according to the finished metal material According to the requirements of the materials, control is carried out throughout the smelting process. For the finished product Al content required to be controlled within 0.008%, avoid adding alloys and slag with high aluminum content in the whole process to achieve alumina mass fraction in inclusions ≤ 20%; for the finished product Al content required to be greater than 0.008%, the Al content in the molten steel at the initial stage of refining is controlled at 0.03%~0.07%, and the alumina mass fraction in inclusions is ≥70%. Through the above measures, the composition and size of non-metallic inclusions in the material can be accurately controlled, thereby improving the purity of the metal material.
[0027] The smelting process mainly controls the initial oxygen content of molten steel in the primary refining furnace, the composition and removal of initial inclusions, and the precise control of the aluminum content in the steel to achieve precise control of the composition and size of non-metallic inclusions in the material, thereby improving the purity of the material. By reducing the oxygen content when the primary refining furnace is tapped and adding deoxidizers, high-melting-point high-alumina and high-silicon oxide inclusions are quickly formed, which quickly collide, aggregate, float and are removed; at the same time, according to the requirements of the finished metal material, the aluminum content is controlled throughout the smelting process to further achieve control of the composition of inclusions. Through the above measures, the equivalent diameter of the inclusions remaining in the metal material is controlled to be distributed in 1-10 microns, which improves the purity of the material.
[0028] In some optional embodiments, the control of the solidification process includes: reducing the carbon activity in the protective slag, setting a reasonable superheat, steel liquid level fluctuation, and nozzle insertion depth to reduce the carbon enrichment of the edge of the ingot by the carbon-rich layer of the protective slag, and combining the reasonable control of superheat, pulling speed, and light reduction parameters to control the segregation index of the ingot to 0.95-1.05.
[0029] In some optional implementations, the carbon activity in the protective slag is controlled in the range of 0.1 to 0.5, the viscosity is in the range of 0.3 to 0.8 Pa·s, the melting point is in the range of 1000 to 1150°C, the thickness of the liquid slag layer is more than twice the liquid level fluctuation, the superheat of the tundish is 20 to 40°C, the liquid level fluctuation is ±3mm, and the nozzle insertion depth variation is controlled within 60mm. Through the above measures, segregation and surface quality control of the ingot solidification process can be achieved.
[0030] The key to the solidification process is to reduce the carbon increase of the edge of the ingot by the carbon-rich layer of the mold slag through the control of the properties of the mold slag, reasonable superheat, steel liquid level fluctuation, and nozzle insertion depth change control. In addition, the ingot segregation index is adjusted to 0.95-1.05 by combining the reasonable control of superheat, pulling speed, and light pressure parameters to improve the uniformity of the original structure.
[0031] In some optional embodiments, the control of the forming process includes: using a strong cooling device to perform high-precision and high-efficiency temperature control, and the temperature control accuracy of each stage from the heating furnace, rough rolling, intermediate rolling, and finishing rolling is within ±50°C, ±30°C, ±20°C, and ±10°C, respectively, to achieve the regulation of austenite grain size, morphology, and carbide precipitation, and control the grain size distribution at 10 to 25 microns, and the carbide particles at 0.1 to 2 microns. Through the above measures, precise control of the organizational uniformity of the ingot rolling process can be achieved.
[0032] The key to rolling forming is to use a strong cooling device for high-precision and high-efficiency temperature control to achieve the regulation of austenite grain size, morphology, and carbide precipitation, and control the grain size distribution at 10-25 microns and the carbide particles at 0.1 to 2 microns.
[0033] In some optional implementations, the control of the deep processing links includes: through spheroidizing annealing ~ drawing, cold extrusion ~ turning and drilling ~ quenching and tempering heat treatment, the depth of the surface decarburization layer of the metal material is distributed in 10 to 20 microns, the heat treatment carbon potential is ≤0.5, and the surface carbon increase index is ensured to be 0.8 to 1.2 and the surface hardness index is 0.80 to 0.85. Through the above measures, the surface structure control of the deep processing process of the casting is achieved.
[0034] The deep processing process mainly controls the depth of the spheroidizing annealing decarburization layer and the carbon potential of the heat treatment process to ensure that the surface carburization index (the ratio of the surface carbon content to the core carbon content) of the finished metal material is as low as 0.8-1.2 and the appropriate surface hardness index (the ratio of the surface hardness to the core hardness) is 0.80-0.85.
[0035] In some optional implementations, the bending strength of the metal material for the motor shaft with high bending resistance is distributed in the range of 350 to 2000 MPa, and the proportion of fractures occurring during the bending test at a specified bending force is ≤1%.
[0036] As can be seen from the above, the embodiment of the present invention provides a method for preparing a metal material for a motor shaft with high bending resistance, which has the following characteristics and advantages:
[0037] (1) Through the control of the composition and key parameters of the production process of this scheme, a metal material for motor shaft with high purity (equivalent diameter of inclusions distributed in the range of 1-10 microns), low ingot segregation index of 0.95-1.05, low surface carbon increase index of 0.8-1.2, and suitable surface hardness index of 0.80-0.85 is prepared, thereby improving the toughness of the metal material and comprehensively realizing the preparation of high-strength and high-toughness metal materials for high-bending motor shafts.
[0038] (2) The smelting process effectively controls the composition, size and quantity of inclusions by precisely controlling the initial oxygen content in the primary smelting furnace and the process aluminum, thereby improving the purity of the material.
[0039] (3) In the rolling process, controlled rolling and controlled cooling process design and precise temperature control are used to achieve the miniaturization of grain and carbide size, providing good uniformity for subsequent cold bending tests.
[0040] (4) The innovative deep processing process reduces the surface hardness by controlling the depth of the decarburization layer during spheroidizing annealing and the carbon potential during the heat treatment process, thereby further improving the cold bending resistance.
[0041] The present invention will be further described below in conjunction with the embodiments.
[0042] Example 1
[0043] A method for preparing a metal material for a motor shaft with high bending resistance comprises the following steps:
[0044] 1. A metal material for a motor shaft with high bending resistance, wherein the chemical composition is C: 1.05wt%, Si: 0.25wt%, Mn: 0.35wt%, Al: 0.012wt%, N: 0.004wt%, Cu: 0.03wt%, As: 0.004wt%, Sn: 0.005wt%, P: 0.015wt%, S: ≤0.002wt%.
[0045] 2. The preparation process includes “primary smelting - ladle refining” smelting, “protective pouring” solidification, “heat rolling” forming, and “spheroidizing annealing - drawing, cold extrusion - turning and drilling - quenching and tempering heat treatment” deep processing.
[0046] 3. The primary smelting furnace uses a converter, the initial oxygen content of the molten steel is 0.015%, and the aluminum iron deoxidizer is added at the initial stage of steel tapping to quickly form high melting point high alumina inclusions, which quickly collide, gather, float and are removed; at the initial stage of refining, the Al content in the molten steel is controlled at 0.05%, and the mass fraction of alumina in the inclusions is 75%. The equivalent diameter of the inclusions remaining in the metal material is distributed in the range of 1-5 microns.
[0047] 4. In order to reduce the carbon-enriched layer of the mold slag during solidification, the carbon activity of the mold slag used is 0.12, the viscosity is 0.35 Pa·s, the melting point is 1050℃, and the thickness of the liquid slag layer is 8mm. The superheat of the tundish is 30℃, the liquid level fluctuation is controlled at ±3mm, and the segregation index of the cast slab is 1.03.
[0048] 5. The temperature control accuracy of heating furnace, rough rolling, intermediate rolling and finishing rolling in the rolling process is ±45℃, ±25℃, ±15℃ and ±5℃ respectively. The grain size of finished products is distributed in the range of 10-25 microns, and the carbide particles are in the range of 0.1 to 2 microns.
[0049] 6. After spheroidizing annealing, the metallographic sample was prepared and etched by nitric acid solution. The depth of the decarburized layer observed under a metallographic microscope with a magnification of 500X was 10-20 microns. Figure 1 The heat treatment carbon potential is 0.2, the surface carbon increase index is 0.9, and the surface hardness index is 0.82. The matrix structure after heat treatment is tempered martensite + carbide. There is a uniform black quenched and tempered structure at the edge, which is consistent with the depth of the decarburized layer after ball erosion, distributed in 10-20 microns. There are fewer white carbide particles, which is consistent with the lower surface carbon increase index. The specific morphology is as follows Figure 2 shown.
[0050] Example 2
[0051] The steps are similar to those in Example 1. In particular, the initial oxygen content of the converter molten steel is 0.025%. To reduce the influence of the initial oxygen content, 0.01% C of carbon powder is added for pre-deoxidation, and then a deoxidizer is added to produce inclusions with a mass fraction of 90% alumina, which are very easy to float and remove. The inclusions remaining in the metal material are fine high-alumina inclusions produced by subsequent secondary oxidation, such as Figure 3 As shown, there is little harm to material properties, and the cold bending cracking rate is only 0.05%.
[0052] Example 3
[0053] The steps are similar to those in Example 1. In particular, the carbon content of the component is 0.45. The solidification process effectively controls the carbon-rich layer of the protective slag to increase carbon on the edge of the ingot. The carbon activity of the protective slag used is 0.1, and no carbon increase occurs on the edge of the ingot. The surface cross-section sample of the processed part is prepared into a metallographic structure and the structure diagram after corrosion is as follows: Figure 4As shown, ferrite and pearlite are evenly distributed, and the cold bending cracking rate is low, only 0.055%.
[0054] Comparative Example 1
[0055] The steps are similar to those in Example 1, except that the depth of the decarburized layer in the spheroidizing annealing process is 5 μm. The hardness distribution of the prepared product is compared with that in Example 1 as shown in the following table. In the cold bending test, the surface hardness is high, the toughness is insufficient and cracking occurs. Figure 5 The metal material prepared in Comparative Example 1 broke during the cold bending test. The secondary electron morphology of the fracture surface shows that the fracture surface of the bending fracture sample is relatively flat, and the crack source is located at the edge of the sample. The metallographic structure of the edge of the metal material prepared in Comparative Example 1 after spheroidizing annealing and heat treatment is further compared and analyzed. Figure 6 and Figure 7 As shown, the depth of the decarburized layer observed under a metallographic microscope at a magnification of 500X after the metallographic sample prepared after spheroidizing annealing in the comparative example was within 10 microns, and the black structure at the edge of the broken part was relatively shallow, about 6-8 microns, and also no more than 10 microns, and there were more white carbide particles, corresponding to a relatively high surface hardness index of 0.86. The comparison is shown in the following table.
[0056] serial number Surface hardness HV5 Core hardness HV5 Surface hardness index Example 1 533 642 0.83 Comparative Example 1 560 645 0.86
[0057] Comparative Example 2
[0058] The steps are similar to those in Example 2, except that the initial oxygen content of the converter molten steel is 0.035%, resulting in a large loss of Al in the early stage of refining, and the Al content is only 0.015%, resulting in a large amount of composite liquid inclusions with a mass fraction of 60.3% of aluminum oxide, such as Figure 8 As shown, it is not easy to remove and remains in the metal material, reducing the purity and increasing the cold bending cracking rate by 2.3%.
[0059] Comparative Example 3
[0060] The steps are similar to those in Example 3, except that the carbon-rich layer of the mold slag was not effectively controlled during the solidification process to increase carbon at the edge of the ingot. The carbon activity of the mold slag used was 0.9, resulting in carbon increase at the edge of the ingot. Fig. 9 As shown, the cold bending cracking rate increased significantly to 9.5%.
[0061] Comparative Example 4
[0062] The steps are similar to those of Example 1, except that the C content is controlled to be higher at 1.45wt%, and the cold bending cracking rate is higher at 5.6%.
[0063] The above are only preferred embodiments of the present invention and are not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A method for preparing a metal material for a motor shaft with high bending resistance, characterized in that: It includes: By carrying out whole-process control from material composition design, preparation to deep processing, the equivalent diameter of inclusions in the metal material for motor shaft is distributed between 1 and 10 microns, the low ingot segregation index is between 0.95 and 1.05, the low surface carbon increase index is between 0.8 and 1.2, and the surface hardness index is between 0.80 and 0.85, thus producing high-strength and high-toughness metal material for motor shaft.
2. The preparation method according to claim 1, characterized in that: Calculated by weight percentage, its chemical composition is as follows: C: 0.35-1.35wt%, Si: 0.10-0.50wt%, Mn: 0.1-1.5wt%, Al: 0.002-0.045wt%, N: 0.002-0.02wt%, Cu≤0.25wt%, As≤0.040wt%, Sn≤0.028wt%, P: ≤0.025wt%, S: ≤0.045wt%, and the rest are Fe and impurities.
3. The preparation method according to claim 1, characterized in that: The control of the preparation process includes: controlling the parameters of the smelting process, solidification process and molding process; the control of the deep processing process includes: controlling the surface structure control of spheroidizing annealing and heat treatment process.
4. The preparation method according to claim 3, characterized in that: The control of the smelting process includes: controlling the initial oxygen content of the molten steel in the primary refining furnace, controlling the initial inclusion composition and removal, and precisely controlling the aluminum content in the steel, so as to control the equivalent diameter of the inclusions remaining in the metal material to be distributed within 1 to 10 microns, thereby achieving purity control of the molten steel during the smelting process.
5. The preparation method according to claim 4, characterized in that: The control of the initial oxygen content of the molten steel in the primary refining furnace includes: controlling the initial oxygen content of the molten steel at 0.01-0.03% by improving the dynamics of the composite bottom blowing of the primary refining furnace and controlling the blowing oxygen consumption. When the initial oxygen content is higher than 0.02%, carbon powder is added in equal proportion for pre-deoxidation; the control of the composition and removal of the initial inclusions includes: the addition of deoxidizers at the beginning of the primary refining furnace quickly forms high-melting-point high-alumina and high-silicon oxide inclusions, which are quickly collided, aggregated, and floated for removal; the precise control of the aluminum content in the steel includes: according to the requirements of the finished metal materials, The whole smelting process is controlled. For finished products with Al content required to be controlled within 0.008%, alloys and slag with high aluminum content are avoided from being added throughout the whole process to achieve alumina mass fraction in inclusions ≤20%. For finished products with Al content required to be greater than 0.008%, the Al content in the molten steel at the initial stage of refining is controlled at 0.03%-0.07%, and the alumina mass fraction in inclusions is ≥70%. Through the above measures, the composition and size of non-metallic inclusions in the material can be accurately controlled, thereby improving the purity of the metal material.
6. The preparation method according to claim 3, characterized in that: The control of the solidification process includes: reducing the carbon activity in the protective slag, setting a reasonable superheat, steel liquid level fluctuation, and nozzle insertion depth to reduce the carbon increase of the carbon-rich layer of the protective slag on the edge of the ingot, and combining the reasonable control of superheat, pulling speed, and light pressure parameters to control the ingot segregation index within 0.95-1.
05.
7. The preparation method according to claim 6, characterized in that: The carbon activity in the protective slag is controlled in the range of 0.1-0.5, the viscosity is in the range of 0.3-0.8 Pa·s, the melting point is in the range of 1000-1150℃, the thickness of the liquid slag layer is more than twice the liquid level fluctuation, the superheat of the tundish is 20-40℃, the liquid level fluctuation is ±3mm, and the nozzle insertion depth variation is controlled within 60mm. Through the above measures, the segregation and surface quality control of the solidification process of the casting can be achieved.
8. The preparation method according to claim 3, characterized in that: The control of the forming process includes: using strong cooling equipment for high-precision and high-efficiency temperature control. The temperature control accuracy of each stage from heating furnace, rough rolling, intermediate rolling, and finishing rolling is within ±50℃, ±30℃, ±20℃, and ±10℃ respectively, to achieve the regulation of austenite grain size, morphology, and carbide precipitation. The grain size distribution is controlled at 10 to 25 microns, and the carbide particles are 0.1 to 2 microns. Through the above measures, precise control of the organizational uniformity of the ingot rolling process can be achieved.
9. The preparation method according to claim 3, characterized in that: The control of deep processing links includes: through spheroidizing annealing ~ drawing, cold extrusion ~ turning and drilling ~ quenching and tempering heat treatment, the depth of the surface decarburization layer of the metal material is distributed in 10 to 20 microns, the heat treatment carbon potential is ≤0.5, and the surface carbon increase index is guaranteed to be 0.8 to 1.2 and the surface hardness index is 0.80 to 0.
85. Through the above measures, the surface structure control of the deep processing process of the casting can be achieved.
10. The preparation method according to any one of claims 1 to 9, characterized in that: The bending strength of the high bending resistance metal material for the motor shaft is distributed in the range of 350-2000 MPa, and the proportion of fractures occurring during the bending test under the rated bending force is ≤1%.